Flexible in-plane micro-supercapacitors: Progresses and challenges in fabrication and applications - Zhang, Panpan; Wang, Faxing; Yang, Sheng; Wang, Gang; Yu, Minghao; Feng, Xinliang (Energy Storage Materials, 2020)
The great popularity of portable, wearable, and implantable smart electronics has intensively boosted the development of flexible miniaturized power supplies. Owing to the fast charge/discharge capability, high power delivery, long cycling lifetime, easy fabrication and integration, flexible in-plane micro-supercapacitors (FPMSCs) are of significance as the micropower sources for the next-generation flexible on-chip electronics. In this review, we provide a comprehensive overview about FPMSCs and discuss the recent advances in their fabrication and applications. Particular emphasis is put on the emergent device fabrication technologies of FPMSCs, including deposition techniques, coating strategies, etching methods, and printing technologies. Moreover, we highlight the unique applications of FPMSCs in constructing smart responses and self-powered integrated systems in terms of multifunctional operation modes. Finally, the remaining challenges regarding flexibility, performance improvement, smart response, and microdevice integration of FPMSCs are discussed, which will stimulate further research in this thriving field.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Flexible in-plane micro-supercapacitors; Microfabrication technologies; Self-powered integrated systems; Smart responses